Harte Arbeit am Begriff: Medienarchäologische Antworten auf die Frage nach der Technologie - Ernst, Wolfgang (Mechane, 2020)
A literal understanding of „technology“ reveals that in this very term a specific technológos is a work. This approach identifies the core drama in contemporary media culture: the operative (sometimes incommensurable) encounters between the symbolic order and physical matter into which logics and codes have to be implemented in order to become operative as media. This entanglement becomes most expressive in digital computing as the technical realization of the abstract Turing maschine. In order to avoid being trapped by the common anthropocentrism in the analysis of technics, media archaeology is proposed as a method which allows for technológos to express itself, in an emancipation from both human „natural“ language, and from conventional, body-related cultural techniques. In critical reference to Hegel, Simondon, and Heidegger‘s „Question concerning Technology“ (and his notion of „enframing“), the focus is radically object- und process-oriented. The Eigensinn – and the Eigenzeit – of technological knowledge is addressed in concrete media-technical scenarios, such as the electronic television image, and clocked timing mechanisms.